Is the justice frame effective in mobilizing support for human rights violations? Evidence from the Philippines. Issue 2 (3rd April 2023) - Calimbahin, Cleo Anne A.; Kasuya, Yuko; Miwa, Hirofumi
Abstract: Effective message framing motivates individuals to act for and defend human rights. What effective message framing motivates individuals to defend human rights? Recent experiment-based framing studies show that personal frames are more successful than informational or motivational frames in increasing the advocacy activities of human rights organizations. This study tested the justice frame using the Philippine case of extrajudicial executions. Employing internet-based survey experiments, we tested the effects of the justice frame on consensus and action mobilizations as well as the three frames mentioned above. Our results showed that combining justice and the personal frame is more effective. We also examined emotions inflicted by framing. Our results reveal an association between empathy and anger as a reaction that connects exposure to personal frame and mobilization.